Effectiveness of video self-instruction training on cardiopulmonary resuscitation retention of knowledge and skills among nurses in North-western Nigeria - Saidu, Ahmed; Lee, Khuan; Ismail, Iskasymar; Arulogun, Oyedunni; Lim, Poh Ying (Frontiers Media, 2023)
Background: Adaptable cardiopulmonary resuscitation/basic life support (CPR/BLS) training are required to reduce cardiac arrest mortality globally, especially among nurses. Thus, this study aims to compared CPR knowledge and skills retention level between instructor-led (control group) and video self-instruction training (intervention group) among nurses in northwestern Nigeria.